Children living in pandemic times: a geographical, transnational and situated view. Issue 4 (4th July 2022) - Cortés-Morales, Susana; Holt, Louise; Acevedo-Rincón, Jenny; Aitken, Stuart; Ekman Ladru, Danielle; Joelsson, Tanja; Kraftl, Peter; Murray, Lesley; Tebet, Gabriela
ABSTRACT: The aim of this editorial to the Viewpoints Special Issue on 'Children Living in pandemic Times: a geographical, transnational and situated view' is, on the one hand, to present a transnational general picture of the COVID-19 situation for children. And on the other, to make a call for childhood researchers particularly focused on children's geographies, to collaboratively approach this unprecedented situation. The main aspects of children living in pandemic times as they are identified by the different viewpoints in this special issue are presented, highlighting key commonalities and differences across countries, discussing the aspects that emerge from this phenomenon that seem most relevant for research on children's geographies in these times. Finally, we refer to some of the studies being conducted in different parts of the world, methodological challenges for children's geographies research under these circumstances, and emerging research questions.